Empowering a Family Welfare Movement Group through Lady Kaka - Hamia Hamia; Irnawati Irnawati; Muhammad Wahyu; Sakina Amaliah Pratiwi; Wahyudin Wahyudin (Jurnal Pengabdian kepada Masyarakat (Indonesian Journal of Community Engagement), 2021)
The program aims to improve the knowledge and welfare of the Family Welfare Empowerment or abbreviated as PKK group through cultivation of Black Soldier Fly (BSF) and reduce organic waste by utilizing it as BSF growing media. Reusing organic waste is an effective way to reduce waste such as vegetables and fruits. Increasing organic waste in Sungguminasa Central Market causes the society needs in knowledge and information on managing the organic waste to become economically valuable products. Based on the observations, the black soldier fly program as fish feed in term (Lady Kaka) was used as main solution because BSF in maggot phase consumes the organic waste. The program involves seven people from PKK group with majority of housewives who do not have fixed income. The implementation of this program consists of 3 phases, namely initial preparation phase which includes observation, administration, and provision of tools and materials, implementation phase which includes training and activation of PKK group, and the last is monitoring and evaluation phase. The results achieved were the transfer of knowledge through training activities to PKK group about BSF cultivation and its management to become fish feed and product marketing to increase the productivity and prosperity of PKK group as well as reducing the trash in Sungguminasa Central Market due to being utilized as growing media of BSF